Needs Analysis of Pop-Up Book Media Development in Learning Theme 8 for Grade V Elementary School with a Scientific Approach - S, Moch Bayu Ibrahim; Pramono, Suwito Eko; Fakhruddin, Fakhruddin; Subali, Bambang (Proceedings of International Conference on Science, Education, and Technology, 2024)
The use of effective learning media is key in improving the quality of learning in grade V, especially in facing the challenges of learning theme 8 with a scientific approach. Pop Up Book is one of the learning media that attracts attention to be used in this learning context. This study aims to analyze the need for Pop Up Book media development in learning theme 8 for grade V SD with a scientific approach. The research method used is a qualitative research design with primary data collection through questionnaires and interviews with fifth grade teachers from three different schools in different areas: SD Negeri Kecomberan 1, SD Negeri 2 Kepompongan, and SDIT Akmala Sabila Cirebon. The results of the analysis show variations in the use of learning media between schools, but there are similarities in efforts to prepare materials according to the curriculum and prepare learning activities. The main challenge faced is limited access to technology, where teachers face difficulties in accessing hardware and lack of knowledge or training in using the media. Nonetheless, efforts have been made to find alternative solutions and support from the school. In conclusion, the development of Pop Up Book media in learning theme 8 of grade V SD with a scientific approach requires a holistic and integrated approach. By taking into account the existing challenges, potentials and needs, as well as with support from the school and collaboration between teachers, the development of learning media can be one of the effective solutions in improving the quality of learning and achieving the learning objectives that have been set.